RELATIONSHIP BETWEEN MATHEMATICS PERFORMANCE AND ENGLISH LANGUAGE PROFICIENCY AMONG SENIOR SECONDARY SCHOOL STUDENTS IN BAUCHI METROPOLIS, NIGERIA - Ibrahim Zainab Tanko; Balarabe Yushau, PhD; Ibrahim Arhyel (Galaxy International Interdisciplinary Research Journal, 2022)
The study investigated the relationship between English language proficiency and mathematics performance among senior secondary school students in Bauchi metropolis. Explanatory correlational research design was used in the study. The population of the study comprised of all the nine thousand and sixty two (9062) SS2 Students within Bauchi metropolis. Three hundred and eighty three (383) SS2 Students were randomly sampled from twenty-two senior secondary school using Stratified Sampling Technique. Yamane-Taro Method of Sample size determination was used in the study. The instruments for data collection were English Language Proficiency Test (ELPT) and Mathematics Achievement Test (MAT). Mean and Standard deviation were used to answer research question 1 and 2 while Pearson Product Moment Correlation Co-efficient was used to answer research questions 3. English language proficiency was found to have positive and significant relationship with mathematics performance of senior secondary school students in Bauchi metropolis. It was recommended among others that Students’ awareness should rest toward understanding the relationship between Language of Instruction and Mathematics performance.